Factors influencing participation among adults aging with long-term physical disability. Issue 1 (January 2022) - Heeb, Rachel; Putnam, Michelle; Keglovits, Marian; Weber, Courtney; Campbell, Margaret; Stark, Susan; Morgan, Kerri
Abstract: Background: People aging with long-term physical disability (AwPD) experience barriers to participation and independent living. There are currently limited evidence-based interventions that address issues regarding participation for people AwPD. Objective: This study examined factors influencing participation in personal and life activities among people AwPD to inform future interventions. Methods: A cross-sectional study within an ongoing, community-based cohort study of participation was conducted. A purposive sample of people AwPD aged 45–65, living with a physical disability for at least five years, and who speak English was recruited through disability organizations, aging organizations, and social media. Participants answered open-ended questions about what supports they needed to successfully participate in nine activity categories derived from the Health and Retirement Study participation items (e.g., employment, community leisure). A content analysis was conducted using NVivo to categorize responses, and member checking occurred with four additional people AwPD. Results: A total of 215 participants completed the survey. Eight categories of factors emerged from the data: physical environment factors, social factors, symptoms, economic factors, policy factors, body structure and functions, mental and emotional state, and temporal factors. Participant responses illuminated a combination of environmental and individual factors. Physical effects of disability and accelerated aging, such as pain and fatigue, paired with environmental factors, such as accessibility of transportation, were reported as influencing participation. Conclusions: People AwPD experience a range of factors that substantially impact their ability to remain independent and participate in society. By identifying barriers to participation, new interventions addressing these barriers may be developed, resulting in more effective service provision, enhanced participation in personal and life activities, and improved health and well-being.